Adaptive containment control for nonlinear strict-feedback multi-agent systems with dynamic leaders. Issue 6 (3rd June 2022) - Cui, Yang; Liu, Xiaoping; Deng, Xin; Wang, Lidong
Abstract : This paper focuses on the adaptive containment control problem for nonlinear strict-feedback multi-agent systems with dynamic leaders. An adaptive controller is constructed by backstepping control, first-order filters and compensating signals. The ``explosion of complexity" phenomenon is avoided by introducing first-order filters in traditional backstepping control, and filter errors are handled with compensating signals. All adaptive laws are accumulated to the last step by using tuning functions. The whole control design method is divided into two parts. One is to design adaptive tracking control for dynamic leaders. The other is to design adaptive containment control for followers. Through the proposed control method, the closed-loop system is stable, and all followers can converge to the convex hull built by the leaders. The simulation studies can confirm the effectiveness of the proposed control method.